CULTURALLY RESPONSIVE TEACHING AND LINGUISTIC AWARENESS AMONG HIGH-PERFORMING EFL TEACHERS: INTERCULTURAL INSIGHTS FROM INDONESIAN ISLAMIC BOARDING SCHOOLS - Fatmawaty, Riryn; Retnaningdyah, Pratiwi; Mustofa, Ali (Veredas do Direito, 2026)
Culturally Responsive Teaching (CRT) is widely recognized as a framework for managing linguistic diversity, cultural identity, and equality in English-as-a-Foreign Language (EFL) settings. This study looks at how high-performing EFL teachers in Indonesian Islamic boarding schools conceptualize and implement CRT using linguistically informed English Language Teaching (ELT) approaches. Using qualitative data from in-depth interviews, classroom observations, and reflective writings, the study examines how twelve teachers incorporate cultural sensitivity, pragmatic awareness, and intercultural communication competence into their daily education. The findings reveal three key aspects of their practice: (1) linguistic-cultural scaffolding that validates students' first-language resources and discourse norms; (2) pedagogical responsiveness through culturally grounded materials, identity-affirming interaction, and intercultural dialogue; and (3) teacher agency in navigating institutional constraints. These teachers view language as both a communicative system and a cultural resource, weighing grammatical precision against intercultural meaning-making. The study contends that high-performing EFL teachers serve as intercultural mediators whose linguistic awareness promotes equal participation and global readiness. Implications include incorporating CRT-linguistics ideas into teacher education, changing curricula to emphasize multilingual repertoires, and increasing institutional support for culturally and linguistically responsive pedagogy. By combining CRT, linguistics, and intercultural communication, the study presents an empirically grounded model of linguistically aware CRT for EFL settings.